A vacuum arc plasma source with extended design. (6th August 2013) - Lisenkov, A. A.; Bystrov, Yu. A.; Vetrov, N. Z.
Abstract A vacuum‐arc plasma source having an extended design, operating in pulse regime and generating directed conveyer‐type flow was created and investigated. The identified regularity of development of arc discharge allowed controlling generation modes of the plasma source, providing the secure fixation of the cathode spots on the working surface and accelerated conversion of the cathode in the working mode. In this case each stage of development of arc discharge is determined by the conditions of existence of the cathode spots on the working surface of the cathode.